2002
DOI: 10.1136/bjsm.36.4.265
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of injuries to elite Australian rugby union players

Abstract: Objectives: To assess injury patterns and incidence in the Australian Wallabies rugby union players from 1994 to 2000. To compare these patterns and rates with those seen at other levels of play, and to see how they have changed since the beginning of the professional era.Methods: Prospective data were recorded from 1994 to 2000. All injuries to Australian Wallabies rugby union players were recorded by the team doctor. An injury was defined as one that forced a player to either leave the field or miss a subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
192
4
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(230 citation statements)
references
References 21 publications
(8 reference statements)
25
192
4
5
Order By: Relevance
“…Contrary to this, a systematic review of eleven studies found that adolescent ball carriers generally sustained more injuries (17 -65%) than tacklers (19 -40%). [14] Injury location Overall, the head sustained the highest injury rate, as also seen in the literature, [7,12,13,15] followed by the face. As there is no clear definition to distinguish between head and face injuries, this could be misinterpreted and should be specified on the injury report form.…”
Section: Tackler and Ball Carrier Injury Susceptibilitysupporting
confidence: 56%
See 1 more Smart Citation
“…Contrary to this, a systematic review of eleven studies found that adolescent ball carriers generally sustained more injuries (17 -65%) than tacklers (19 -40%). [14] Injury location Overall, the head sustained the highest injury rate, as also seen in the literature, [7,12,13,15] followed by the face. As there is no clear definition to distinguish between head and face injuries, this could be misinterpreted and should be specified on the injury report form.…”
Section: Tackler and Ball Carrier Injury Susceptibilitysupporting
confidence: 56%
“…Literature reports the tackle to be the most dangerous phase of play as 40 -64% of injuries were sustained as a result of a tackle. [5,7,8,12] This also holds true for koshuis rugby based on the data presented here.…”
Section: Tackle-related Injury Ratesupporting
confidence: 54%
“…The increasing intensity, frequency of impact and consequent effect upon joint stability may be the underlying rationale behind the tendency for increasing injury occurrence in the game as a whole, and the distribution of injury occurrence biasing toward the final quarter of the game (Bathgate et al, 2002). With such information, coaches and medical teams can begin to address the modifiable factors, with consideration to sensory motor function training at the outer and inner ranges, and not just morphological orientated training.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In this study, the incidence of knee injuries in collegiate rugby union players was similar to that reported in professional players. Several previous studies demonstrated that the incidence of injury increases with an increase in the competition level and age [11][12][13] . Bathgate et al reported that, among Australian rugby players, the incidence of injuries increased after entering the professional system 12) .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies demonstrated that the incidence of injury increases with an increase in the competition level and age [11][12][13] . Bathgate et al reported that, among Australian rugby players, the incidence of injuries increased after entering the professional system 12) . In addition, after comparing the incidence of injuries among ages, Haseler et al demonstrated that the incidence of injuries increased with age 13) .…”
Section: Discussionmentioning
confidence: 99%